(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Haemorrhoid is the frequent problem in clinical practice of general surgery. Haemorrhoids are dilatation and tortuosity of rectal veins affecting almost 4.5% of the population. Various operative and non operative therapeutic options are in practice to treat haemorrhoids, yet none has been proven cent percent effective. Sclerotherapy is a simple, safe and cost effective procedure that is widely practiced globally to treat haemorrhoids. Many sclerosants are being used with variable efficacies. Objective: To evaluate the outcome of injection Sclerotherapy in first degree and second degree haemorrhoids. Materials and Methods: Fifty patients of both gender having haemorrhoids who attended Outpatient Department (OPD) at BNS Patenga from September 2013 to August 2014 were included in this study. On the basis of history, patients were selected for Digital Rectal Examination (DRE) and proctoscopic examination to confirm the diagnosis. Sclerotherapy was repeated at interval of 6 weeks till symptomatic relief was achieved. Maximum 3 sittings of sclerotherapy were given. Patients were followed up at 3 months interval for 1 year. Results: This prospective study was conducted on 50 cases of first degree and second degree Haemorrhoids. The highest number of patients 21(42%) were in the age group of 21-30 years with majority 38(76%) being male. Male female ratio was 3.16: 1. All the patients presented with painless per-rectal bleeding. Satisfactory results were observed in 29(58%) patients of whom 20(40%) patients were having first degree haemorrhoids and 9(18%) patients were having second degree haemorrhoids. Sclerotherapy was more effective in first degree compared to second degree haemorrhoids patients. Conclusion: Injecting Sclerotherapy is a suitable office procedure for treatment of haemorrhoids. The method is easy, convenient, cheap, well accepted and comfortable for patient. More or less there are no complications and the result is also satisfactory. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 98-101